Peran intensitas komunikasi dan regulasi emosi terhadap konflik interpersonal pada dewasa awal yang menjalani hubungan berpacaran jarak jauh - Aryaningsih, Putu Indira Ayu; Susilawati, Luh Kadek Pande Ary (Jurnal Psikologi Udayana, 2020)
Courtship is a relationship that involves a greater and deeper intimacy and romantic feelings between two individuals who know each other. During the process, courtship cannot always be done closely due to education and careers in different areas that causes long distance relationship. The distance becomes an obstacle which triggers several conflicts. The situation of conflict always involves the communication process and emotional aspects. The influent communication tends to cause misunderstanding that lead to conflict. Uncontrolled emotion causes a dangerous conflict. This study applied quantitative method that discussed the role of communication intensity and emotion regulation toward interpersonal conflict at early adulthood undergoing long distance relationships. The subjects of study involved 307 adults who had long distance relationships. In this study, the scale of interpersonal conflict, communication intensity, and emotional regulation were applied as measuring instruments. Multiple regression technique was use to do data analysis. The results of multiple regression tests showed that a regression coefficient was 0,596; a coefficient value of determination was 0,355; and a significance value was 0,000 (p<0,05) with a standardized beta coefficient on the variable of communication intensity about -0,373 and emotion regulation about -0,348. These results indicate that communication intensity and emotion regulation take a role to decrease interpersonal conflict at early adulthood who have long distance relationships.